Studies on Transient Processes under Excitation of Ultrashort Laser Pulses in Colloidal Solutions of CdSe/ZnS Quantum Dots - Danilov, Vladimir V.; Kulagina, Anastasia S.; Sibirev, Nickolay V. (Research Trends and Challenges in Physical Science Vol. 5, 2021)
Earlier we concluded, that RSA (reverse saturable absorption) is the main mechanism of optical limiting in CdSe/ZnS QDs by nanosecond pulses acting, which is accompanied by " light quenching " simultaneously . The reduction of the pulse duration fundamentally changes the limiting kinetics and OL mechanisms [1,2,3]. Free carriers absorption became significant in the case of ps-pulses and intense light. We present, that in the case of picosecond durations, the limitation efficiency of laser radiation and absorption kinetics in CdSe/ZnS colloidal solutions are determined by the Auger relaxation through the 1S(e) states. A "delayed limitation" effect has been identified in the measured kinetics of a probe-pulse transmission. The competition between the following two relaxation processes of highly excited states, relaxing through size quantization levels and phononless relaxation through traps states, has been identified using numerical modelling.